Is Profitability Affected By Carbon Emission Disclosure? - Fitriani, Nosilia (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
So far, in testing the effect of carbon emission disclosure on financial performance, only using financial performance based on net income, there have not been many studies that specifically examine the effect of carbon emission disclosure on financial performance based on operating profit, comprehensive profit and attributable profit, even though these three profits are presented in the income statement. The purpose of this study is to test the effect of carbon emission disclosure on profitability based on operating profit, comprehensive profit and attributable profit. The data for this study are secondary data from the annual reports and sustainability reports of companies listed on the IDX for the period 2019 - 2024 with a total of 2,960 observation data. Hypothesis testing uses multiple linear regression analysis. The results of the study indicate that carbon emission disclosure has a positive effect on profitability, as measured by ROA operating profit, comprehensive profit and attributable profit. The results of this study are consistent with the stakeholder theory that carbon emission disclosure is not only in the interests of the government and the environmentally conscious community, but also shareholders and creditors because it has been proven to have an impact on profitability. The originality of this study lies in testing the effect of CED on three types of modified ROA formula profits, namely operating profit, comprehensive profit and attributable profit.